Analisis Tingkat Kecemasan Matematis Siswa Sma Ditinjau Dari Sudut Pandang Neurosains - Lyany, Elisabeth Gunu (Universitas Nusa Cendana, 2024)
This study aims to analyze the level of mathematics anxiety and the factors that cause mathematics anxiety in terms of neuroscience. The research method used is qualitative research with a qualitative descriptive approach. The research subjects were 31 students of class XII of SMA Swasta Bintang Timur 1 Balige. Data on the level of math anxiety was obtained through a literature study assisted by a questionnaire to determine the factors that affect math anxiety according to neuroscience. The results showed that 18 students experienced high levels of math anxiety and 13 other students experienced moderate levels of math anxiety. Students experience the most math anxiety from a cognitive perspective as shown by a percentage of 37.1% and the symptoms that are often felt are often forgetting formulas and feeling overwhelmed when doing math tasks that require a high level of thinking. From a neuroscience point of view, cognitive math anxiety is influenced by the neocortex; math anxiety based on personality factors is influenced by the autonomic nervous system; and math anxiety from social factors is influenced by the anterior cingulate cortex (ACC) brain network. Keywords: Analysis, Math Anxiety, Neuroscience.